Forecasting model based on morphological characteristics for yield of konjac (Amorphophallus muelleri Blume) planted in Tak province, Thailand - Wongpinta, Takdanai; Mianmit, Nittaya; Pothitan, Rachanee; Lumyai , Pichit; Mealim, Somporn (Agriculture and Natural Resources, 2024)
Importance of the work: The useful part of konjac (Amorphophallus muelleri Blume) is its tuber; however, it is difficult to estimate its annual production without weighing the tubers. The newly developed forecasting model aims to provide valuable insights and support decision-making processes related to productivity management, marketing and crop planning. Objectives: To study the relationship between konjac tuber weight and vegetative morphological factors. Materials & Methods: Data were collected from 163 individual konjac plants growing in sample plots. The vegetative morphological factors measured were: stem diameter at ground level, stem height, length of the longest leaf, crown cover, number of bulbils, tuber diameter and tuber weight. A model was developed to forecast konjac productivity using stepwise multivariate regression. Results: The study identified correlations between the vegetative morphological factors of A. muelleri, with the stem diameter at ground level (D0) being the most reliable factor. The equation used to predict A. muelleri tuber weight (Y) was log Y = –3.34 + 2.17 log D0, which had a high coefficient of determination (0.95, p < 0.01). However, this equation was specific to A. muelleri productivity in Tak province. Main finding: The developed equation should be valuable for tuber weight estimation without the need for tuber extraction. It should assist stakeholders to meet market demand.